2017
DOI: 10.3390/w9060386
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Removal of Nonylphenol Ethoxylates and Nonylphenol from Textile Wastewater—A Comparison of a Cotton and a Synthetic Fiber Factory in Vietnam

Abstract: Abstract:The textile industry is a significant source of nonyphenol and their ethoxylates, which are suggested to be responsible for endocrine disruption in wildlife and humans. This study is a comparison of two conventional wastewater treatment processes in a cotton and a synthetic fiber factory in Vietnam, with regard to the distribution and removal of nonyphenol ethoxylates and nonyphenol throughout each process. Diverse trends in the distribution of nonyphenol ethoxylates in wastewater from factories, dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 123 publications
0
6
0
Order By: Relevance
“…A study by Greenpeace outlined that NPs and NPEs are among the most detected chemicals found in wastewater treatment plants. The countries examined in this study were Thailand, China, Mexico and Indonesia (Ho and Watanabe, 2017).…”
Section: Legislationmentioning
confidence: 99%
“…A study by Greenpeace outlined that NPs and NPEs are among the most detected chemicals found in wastewater treatment plants. The countries examined in this study were Thailand, China, Mexico and Indonesia (Ho and Watanabe, 2017).…”
Section: Legislationmentioning
confidence: 99%
“…These nonionic surfactants were recognized as organic priority hazardous substances by the European Union that contain the Endocrine disrupting chemicals (EDCs) group. Adverse effects of NP on immune, reproductive and central nervous systems have been exposed in humans, birds, rats, fish, etc [5–7] . So, it is important to develop an accurate and ultrasensitive procedure for the detection of NP residue in food and aqueous environments [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Adverse effects of NP on immune, reproductive and central nervous systems have been exposed in humans, birds, rats, fish, etc. [5][6][7] So, it is important to develop an accurate and ultrasensitive procedure for the detection of NP residue in food and aqueous environments. [8] Nowadays, the removal of NP pollutants in water and wastewater has gained significant attention due to their adverse impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Nonylphenol ethoxylates (NPEs) and derivatives are widely used in industrial applications as detergents, dispersing agents, paints, plastics, pesticides, emulsifiers, and demulsifiers, and so on. NPEs are non-ionic surfactants, unstable, and biotransformed to metabolites such as nonylphenol monoethoxylate (NPE1), nonylphenol diethoxylate (NPE2), and nonylphenol triethoxylate (NPE3) nonylphenols (NPs) in the aquatic environment (Ho & Watanabe 2017). NPEs have estrogenic properties and a hydrophobic nature so they are highly toxic to human health and organisms (Soares et al 2008).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…NPs concentration was observed as 14 μg/L in the effluent of a textile factory in China (Brigden et al 2011), and 0.5-1.1 μg/L in sewage treatment plants in Japan (Nakada et al 2006). In Vietnam, NP was detected in urban surface water sources with the concentration of 0.025-0.160 μg/L in Hanoi and 0.026-0.149 μg/L in Ho Chi Minh city (Ho & Watanabe 2017). Consequently, to have safe drinking water supplies, the removal of NPEs and derivatives should be carefully considered.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%